MCO breathes new life into the environment - Siti Nur Azwin, Zulkapri (Sun Media Corporation Sdn. Bhd., 2020)
KUALA LUMPUR: The implementation of the Movement Control Order (MCO) due to the Covid-19 pandemic has not only brought about a new normal in the lives of the people, but it has also breathed new life into the environment.